CLEVER maternity care: A before-and-after study of women's experience of childbirth in Tshwane, South Africa - Sarie J. Oosthuizen; Anne-Marie Bergh; Jackie Grimbeek; Robert C. Pattinson (AOSIS, 2020)
Background: Birthing care matters to women and some women experience mistreatment during childbirth. Aim: To determine the effect the 'CLEVER Maternity Care' package, a multi-faceted intervention to improve respectful, quality obstetric care. Setting: Ten midwife-led obstetric units in Tshwane health district, South Africa; five intervention and five control units. Methods: We conducted an anonymous baseline and end-line survey to measure the change in women's perceptions and experiences of childbirth care after the implementation of the CLEVER package. A convenience sample of women returning for a postnatal follow-up visit was obtained at baseline (n = 653) and after implementation of CLEVER (n = 679). Results: Six survey items were selected as proxies for respectful clinical care. There was no significant change in proportions of responses regarding one question, and with regard to patients receiving attention within 15 min of arrival, both the intervention and control group units showed a significant increase in positive responses (odds ratios of 8.4 and 6.1, respectively, and p values of 0.0001 and 0.0007). For the remaining four items (asking permission before doing an examination, positive communication, respectful treatment and overall satisfaction), only the intervention group showed a significant positive change (odds ratios ranging from 2.4 to 4.3; p ≤ 0.0018), with no significant change for the control group (odds ratios between 1.0 and 1.8; p ≥ 0.0736). Conclusion: After the implementation of CLEVER Maternity Care, women reported a more positive experience of childbirth. The CLEVER intervention is a potential strategy for addressing respectful, quality obstetric care that warrants further investigation.